If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 75 = 360 Reorder the terms: 75 + 3x = 360 Solving 75 + 3x = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + 3x = 360 + -75 Combine like terms: 75 + -75 = 0 0 + 3x = 360 + -75 3x = 360 + -75 Combine like terms: 360 + -75 = 285 3x = 285 Divide each side by '3'. x = 95 Simplifying x = 95
| -2a+15-4b= | | 2a+15-4b= | | x+31+29=90 | | Y=3.4x-0.2 | | 8(x+5)=2(4x+1)+38 | | 725=15n+5 | | 26=7x+6-(-3x) | | 2x+128=180 | | 8(3x-7)=2(12x+8) | | A*6+4=14 | | 2g^3h^3/14g | | 88/3-8 | | 14+7a=28 | | 32-8/3 | | 9x/x^2 | | x^2+7x+44= | | (x-7)*7=6x-6 | | 2(4x-1)=3(x+2)+5 | | f(-4)=4x-2 | | 65327=.8x | | c=24n+4 | | 6(x-11)=15-14x | | 6x+6x+2+7=4x+5+7x | | 3x-1/x-4 | | 460=24n+4 | | 6y-2(y+1)=(y-2)+6 | | 7x+11=3(x+y) | | (3d)(3d)(d-7)=0 | | X+(X*0.75)=608 | | 5(x-4)-(12-x)=11+6(1+x) | | 28b-21/7 | | 78=15+21b |